PENINGKATAN PENGETAHUAN IBU ANAK YANG BERESIKO STUNTING TENTANG KESEHATAN GIGI DAN MULUT DENGAN MEDIA LIEFLET - Pinat, Leny Marlina A.; Pay, Mery Novaria; Eki, Yansestina Erlince; Ratu, Antonius Radja; Nubatonis, Mekisedek O. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Stunting is a condition where a child under 5 months of age or is often considered a toddler and has a shorter height or length than a normal child of the same age. The World Health Organization (WHO) defines stunting as a height that is two standard deviations lower than the child's growth and development target. Stunting toddlers are also commonly referred to as short toddlers, this can be seen by measuring the length or height of the toddler with results below normal. Based on data from the 2021 Indonesian Nutritional Status Study (SSGI), the prevalence rate of stunting in NTT reached 37.8 percent or the highest of all provinces in the country. This percentage is also still below the national stunting rate, which is 24.4 percent. based on prevalence, the five provinces with the highest stunting rates are East Nusa Tenggara at 35.3 percent. Based on data on the distribution of stunting in Kupang City 25.1 percent Kupang Regency at 24.1 percent, still higher than the national figure. Factors that influence stunted growth (stunting) include maternal factors: maternal nutritional status during pregnancy, maternal education level, maternal knowledge level, breastfeeding, other factors (MP-ASI), infection factors, family economic factors and environmental factors. Parents, especially mothers, must have good knowledge and awareness in maintaining children's dental health. Children whose parents have low knowledge about proper oral hygiene are at higher risk of experiencing dental caries than children whose parents have better knowledge. One approach that can be taken to improve maternal knowledge is to provide information that is easy to understand and apply, one of which is through leaflets